THE USE OF MODAL AUXILIARY VERBS IN REPORTING COVID-19: A STUDY OF SELECTED ARTICLES DAILY NATION NEWSPAPER - Odhiambo, Kenneth; Odhiambo, Owala Silas (International Journal of Research -GRANTHAALAYAH, 2020)
This article analyses the uses of modal auxiliary verbs in reporting Covid-19 in selected articles in Daily Nation newspaper. Covid-19 is a member of the beta coronaviruses that can cause acute severe respiratory symptoms or possibly mild, cold-like symptoms. The reporting of the disease was done in the newspaper in Kenya every day from the first time it was reported in the country on 13th March 2020. The articles analyzed were purposively selected from articles in Daily Nation newspaper and analyzed using insights from Quirk et al’s (2000) dichotomy of modal auxiliary verbs. The data was analyzed manually with regard to different functions of the modal auxiliary verbs in question. Six categories of modal auxiliaries namely; Ability, possibility, prediction, obligation, intention and quasi-legal modals characterized the data. Findings indicate that the authors of the articles chose predictive auxiliary modals will, may, can and should in that order in the articles. Other types of modal used are would, must and might. The modals used presented the opinions of the article writers and the use of will reported the highest frequency.